Sciaphila kozushimensis (Triuridaceae), a new mycoheterotrophic plant from Kozu Island, Izu Islands, Japan, based on morphological and molecular data - Suetsugu, Kenji; Kinoshita, Akihiko (Phytotaxa, 2020)
A new species of Sciaphila (Triuridaceae), S. kozushimensis Suetsugu, is described from Kozu Island, Izu Islands, Japan. The new species is similar to S. tosaensis in having unisexual flowers (the female towards the base of the rachis), perianth-segments without any appendages and club-shaped style that is as long as or slightly exceeds ovary in the flowering stage. However, it is distinguishable by smaller male flowers, wide and acuminate male perianth segments and somewhat dissimilar perianth segments. An illustration and molecular analysis based on ITS sequences of the new species are provided. A key to the Japanese Sciaphila is also provided for identification of these rare mycoheterotrophic plants.